Brewery industry-led seed sector development for sorghum in Tanzania - Kalema, Elizabeth Phineas; Kimbi, Thedy; Akpo, Essegbemon; Kongola, Eliud; Alex, Gerald; Nzunda, Joseph; Okori, Patrick; Ojiewo, Christopher Ochieng (International Crops Research Institute for the Semi-Arid Tropics, 2022)
The use of sorghum improved variety seeds has been low among sorghum farmers in Tanzania. Due to this, stakeholders such as brewing companies have launched various initiatives to expand the use of improved sorghum seeds. In general, this study was undertaken to assess the contribution of brewing industry to the sorghum value chain in Tanzania. Specifically, this study aims to determine the extent of use of sorghum in brewing (by quantifying the amount of sorghum grain sold to brewing companies and grain off-takers), identifying stakeholders in the value chain, and the impact of the brewing industry on use of improved seeds by smallholder farmers. The study was conducted in 11 districts in 6 regions of Tanzania covering sorghum farmers, grain off-takers, brewing companies, extension officers, and seed producers. Purposive and simple random sampling was used to select respondents: 591 individual farmers, 160 farmers from 16 focus groups, 15grain off-takers, 14 extension officers, 4 Quality Declared Seed (QDS) producers, and 2 brewing companies. Data was then analyzed using descriptive analysis statistics, Probit Regression, and cost-benefit analysis